Proanthocyanidin Polymer-Rich Fraction of Stryphnodendron adstringens Promotes in Vitro and in Vivo Cancer Cell Death via Oxidative Stress - Kaplum, Vanessa; Ramos, Anelise C.; Consolaro, Marcia E. L.; Fernandez, Maria A.; Ueda-Nakamura, Tânia; Dias-Filho, Benedito P.; Silva, Sueli de Oliveira; de Mello, João C. P.; Nakamura, Celso V. (Frontiers in Pharmacology, 2018)
Cervical cancer is the fourth most common cancer that affects women, mainly through human papilloma virus (HPV) infection with high-risk HPV16 and HPV18. The present study investigated the in vitro anticancer activity and mechanism of action of a proanthocyanidin polymer-rich fraction of Stryphnodendron adstringens (F2) in cervical cancer cell lines, including HeLa (HPV18-positive), SiHa (HPV16-positive), and C33A (HPV-negative) cells, and also evaluated in vivo anticancer activity. In vitro, cell viability was determined by the MTT assay. Cell migration was determined by the wound healing assay. The mechanism of action was investigated by performing ultrastructural analysis and evaluating reactive oxygen species (ROS) production, mitochondrial metabolism, lipoperoxidation, BCL-2 family expression, caspase expression, and DNA and cell membrane integrity. In vivo activity was evaluated using the murine Ehrlich solid tumor model. F2 time- and dose-dependently reduced cell viability and significantly inhibited the migration of cervical cancer cells. HeLa and SiHa cells treated with F2 (IC50) exhibited intense oxidative stress (i.e., increase in ROS and decrease in antioxidant species) and mitochondrial damage (i.e., mitochondrial membrane potential depolarization and a reduction of intracellular levels of adenosine triphosphate). Increases in the Bax/BCL-2 ratio and caspase 9 and caspase 3 expression, were observed, with DNA damage that was sufficient to trigger mitochondria-dependent apoptosis. Cell membrane disruption was observed in C33A cells (IC50 and IC90) and HeLa and SiHa cells (IC90), indicating progress to late apoptosis/necrosis. The inhibition of ROS production by N-acetylcysteine significantly suppressed oxidative stress in all three cell lines. In vivo, F2 significantly reduced tumor volume and weight of the Ehrlich solid tumor, and significantly increased lipoperoxidation, indicating that F2 also induces oxidative stress in the in vivo model. These findings indicate that the proanthocyanidin polymer-rich fraction of S. adstringens may be a potential chemotherapeutic candidate for cancer treatment.